A wide-angle circularly polarized tapered-slit-patch antenna with a compact rectifier for energy-harvesting systems [antenna applications corner] - Ang, Ming Jie (2021)
A tapered-slit-patch antenna with wide-angle circularly polarized (CP) radiation and a compact rectifier was investigated for energy-harvesting systems. A tapered-slit octagonal-shaped patch radiator was implemented to realize the CP microstrip antenna with wide-angle radiation using a proximity-coupled feed. Eight tapered slits with length difference of 1.3% were embedded along the octagonal directions symmetrically on the microstrip radiator from the patch's center. The antenna prototype showed a gain of more than 5.8 dBic across the CP bandwidth of 7 MHz (894-901 MHz) with a 3-dB axial ratio (AR) beamwidth of more than 180°. A compact composite right/left-handed (CRLH)-based rectifier operating at 900 MHz was designed to be used along with the antenna for radio-frequency (RF) energy-harvesting system. A microstrip line forms the righthanded part of the CRLH transmission line (TL), and the lumped components form the left-handed part of the CRLH TL. The proposed rectifier was compact with size of 0.18λ ₀ × 0.075λ ₀ × 0.0002λ ₀ at 900 MHz with a high RF-dc conversion efficiency of 43%.